Women Empowerment in Agriculture and its Dimensions: A Conceptual Review - Sharma, Deepika; Chaudhary, Rashmi; Kumar, Krishan (International Journal of Economic Plants, 2020)
Women empowerment is a broader term which has been described in a variety of ways. It is a global issue, which has been accelerated in recent decades. The term women empowerment has also received much attention from researchers, government and other stakeholders. It is now widely accepted that gender equality and women empowerment are essential component for achieving development results. The present article is an attempt to develop conceptual clarity of the term women empowerment and its dimensions in agriculture. As per the existing literature it has been reviewed that women empowerment is a complex and multidimensional concept. Different dimensions of women empowerment resulting from various definitions are: input in productive decisions and autonomy in production, ownership of assets and access to and decisions on credit, control over use of income, workload and time allocation and education. It has also been analysed that access to these dimensions and women empowerment might lead toward sustainable development in terms of improved livelihood resulting in reducing food insecurity.